2022
DOI: 10.1021/acs.nanolett.2c02064
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplex-Proximized Aptamers (G4PA) Efficiently Targeting Cell-Surface Transferrin Receptors for Targeted Cargo Delivery

Abstract: DNA-assembled multiaptamer systems have been demonstrated to significantly promote the aptamer capacity of binding cell-surface-expressed proteins. However, how to conveniently harness them for efficient transmembrane delivery of targets remains a challenge. Toward this goal, here we engineer a G-quadruplex-proximized aptamer (G4PA) system in which a DNA aptamer specific for transferrin receptor (TfR) is guided by a bimolecular G4 and assembles into a dimerized proximity form that well matches homodimeric TfR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…2(d)). [40][41][42][43] It is noteworthy that the polyvalent structure is more efficient than the monovalent structure in identifying the target, or promoting cell-cell recognition. 44 In addition, the combination of static DNA nanostructures with stimulus-response components can be assembled into dynamic DNA nanostructures.…”
Section: Dna Nanostructuresmentioning
confidence: 99%
“…2(d)). [40][41][42][43] It is noteworthy that the polyvalent structure is more efficient than the monovalent structure in identifying the target, or promoting cell-cell recognition. 44 In addition, the combination of static DNA nanostructures with stimulus-response components can be assembled into dynamic DNA nanostructures.…”
Section: Dna Nanostructuresmentioning
confidence: 99%
“…Transferrin receptor (TfR) is a cell-surface-located transmembrane protein involved in intracellular iron transport and typically overexpressed in many cancer cells. Studies have showed that high expression of TfR is associated with increased demand for iron in cancer cells, and it has been an attractive target for targeted delivery in cancer treatment . Recently, TfR aptamers with high affinity toward TfR have been screened, which could readily get inside the cells via clathrin-mediated endocytosis, enabling its use in cancer-targeted therapies. Although transferrin-modified MSNs for drug delivery have been previously reported, , aptamers exhibit more promising clinical applications than proteins because of their advantages of lower cost, more stable chemical properties, easier accessibility, and lower immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…[17] In particular, our recent work shows that G4-proximized transferrin receptor (TfR) aptamers can better match TfR on the surface of cancer cells and exhibit excellent super-transmembrane transport capabilities. [18] Moreover, even in complex biological environments, G4s can bind a large amount of molecular ligands with high affinity, often accompanied by changes in fluorescence properties. [19,20] Of particular interest is that, as reported previously [21,22] and we show here, ligand binding significantly promotes the nuclease-resistant capacity of DNA scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…[29] In this DNA scaffold (ApG4), the TfR aptamer is induced to be dimerized in a proximity state, contributing to super transmembrane efficiency as compared to the monomeric. [18] Furthermore, LDCs, sodium nitroprusside (SNP, NO donor), [30] and doxorubicin (DOX) [31] were loaded into ApG4 in one pot to construct the final smart prodrug system ApG4/LDCs. Under high levels of TfR, GSH, and NOXs in tumor cells, ApG4/LDCs first enter the cancer cells efficiently, and then generate NO and O 2…”
Section: Introductionmentioning
confidence: 99%